The level of school principals' practice of educational leadership in the Sultanate of Oman - AL Ghafri, Hamed Hamood; Bin Sama, Rosni; Abdul-Rahman, Asma (Journal of Educational and Psychological Sciences, 2020)
The study aimed to identify school principals' level of practicing educational leadership in the Sultanate of Oman. It also aimed to analyses differences in this level depending on the gender and the educational governorate. To achieve the purposes of the study and answer its questions, a descriptive approach was used, in addition to the Scale of the Educational Leadership Ability of Mohamed Mounir Morsi. This scale aims to measure the educational leadership ability with its main components that are confirmed by educational administration learners and researchers, namely: (objectivity, use of authority, flexibility, understanding others, and knowledge of principles of communication). The sample of the study consisted of (336) principals (male and female) from the various governorates of the Sultanate.And the research arrived at the following results: the level of school principal's educational leadership practice in the Sultanate of Oman is average as the arithmetical average of school principals' responses for their educational leadership practice level is 0.6. Regarding the level of school principals' practice of educational leadership dimensions, the level of their capabilities in understanding others and educational leadership objectivity id high. As for the level of school principals using the dimensions of the use of authority, knowledge of communication principles and flexibility came at an intermediate level. The results also showed that there are not substantial differences in the level of school principals employing educational leadership dimensions representing in using power, flexibility and understanding others depending on the gender. The results pointed out that there are no statistical differences between all the educational leadership dimensions, depending on the educational governorate except the use of authority who's its results were in favor of school principals in Al Buraimi educational governorate.Based on the results, a number of recommendations and suggestions were presented to improve the level of school principals' practice of educational leadership in the Sultanate of Oman. One of the major recommendations is caring about school principals' educational leadership skills training in particular the skills in which the results showed that the level of school principals' practice is average. These skills are using power, flexibility and knowing communication principles
Keywords: educational leadership ability; School principals; Sultanate of Oman